Stres zawodowy fizjoterapeutów - badania w wybranych oddziałach szpitalnych = Physiatrists’ occupational stress - research in selected hospital wards - Humeniuk, Ewa; Dąbska, Olga; Pawlikowska-Łagód, Katarzyna (Journal of Education, Health and Sport, 2016)
Humeniuk Ewa, Dąbska Olga, Pawlikowska-Łagód Katarzyna. Stres zawodowy fizjoterapeutów - badania w wybranych oddziałach szpitalnych = Physiatrists’ occupational stress - research in selected hospital wards. Journal of Education, Health and Sport. 2016;6(6):375-394. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55776 http://ojs.ukw.edu.pl/index.php/johs/article/view/3589 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Stres zawodowy fizjoterapeutów - badania w wybranych oddziałach szpitalnych Ewa Humeniuk Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie,Poland Olga Dąbska Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie, Poland Katarzyna Pawlikowska-Łagód Zakład Etyki i Filozofii Człowieka, Uniwersytet Medyczny w Lublinie, Poland Słowa kluczowe: stres zawodowy, ochrona zdrowia, fizjoterapeuci, sytuacje trudne, psychospołeczne zagrożenia zawodowe. Streszczenie Wstęp. Stres uważany jest za jeden z głównych determinantów wpływających destruktywnie na środowisko pracy. Stres w pracy to główne zagrożenie dla zdrowia oraz bezpieczeństwa pracowników niemalże wszystkich profesji. Szczególnym zainteresowaniem ostatnimi czasy opatrzono pracowników służby zdrowia, mimo to w polskiej literaturze przedmiotu liczba doniesień na temat stresu w zawodzie fizjoterapeuty jest znikoma. Cel pracy. Ocena stresu zawodowego i sposobów radzenia sobie przez fizjoterapeutów pracujących na oddziale dziecięcym i dziennej rehabilitacji dla dorosłych szpitali Polski wschodniej. Materiał i metody. Badania przeprowadzono na grupie 50 fizjoterapeutów. Narzędzia badawcze stanowiła autorska ankieta stworzona na potrzeby pracy oraz Kwestionariusz Subiektywnej Oceny Pracy autorstwa Dudka i wsp. Wyniki. Osoby posiadające dłuższy staż pracy odczuwają wyższy poziom stresu niż mniej doświadczeni fizjoterapeuci. Najbardziej stresogennymi czynnikami w zawodzie fizjoterapeuty są kontakty społeczne, poczucie zagrożenia i odpowiedzialności, uciążliwości fizyczne. Stwierdzono, że wraz ze wzrostem poziomu wykształcenia wzrasta nasilenie stresu w pracy. Fizjoterapeuci, mający zainteresowania, uprawiający sport, ćwiczenia relaksacyjne, posiadający wsparcie w rodzinie lepiej radzą sobie ze stresem. Jednakże niechętnie korzystają z pomocy psychologa, terapeuty czy psychiatry w walce ze stresem. Wnioski. Poziom stresu odczuwanego przez fizjoterapeutów pracujących zarówno z dziećmi, jak i osobami dorosłymi jest wysoki. Wskazuje to na potrzebę wsparcia tej grupy zawodowej i zwiększenia umiejętności radzenia sobie w stresowych sytuacjach. Physiatrists’ occupational stress - research in selected hospital wards Key words: occupational stress, healthcare, physiatrists, difficult situations, psychosocial work-related hazards. Summary Introduction. Stress is considered to be one of the main determinants affecting workplace in a negative way. Stress in workplace is the main health and security hazard for workers of almost every profession. Lately special focus was put on the health service workers. However, in the polish subject literature reports about stress in the profession of physiatrist is transitory. Goal of work. Assessment of occupational stress and ways of dealing with it physiatrists’ working on the children’s ward and the Daily Rehabilitation Centre of hospitals eastern Polish. Data and methods. The survey was conducted on the group of 50 physiatrists. Authorial survey created for this work and Subjective Work Assessment Questionnaire were the research tools. Results. People with bigger work experience are exposed to higher level of stress than less experienced physiatrists. The most stressful factors in the profession of physiatrist are: social contacts, sense of danger and responsibility, physical nuisances. It was concluded that stress rises along with work experience. Conclusion. The stress level of physiatrists working with both adults and children is high. It highlights the need to support this profession and to develop skills that would help this group in dealing with stressful situations. Physiatrists who have hobbies, play sports, do relaxation exercises and who have family support deal better with stress. However, they’re not very keen on seeking the help of a psychologist, a therapist or a psychiatrist when dealing with stress.